Proceedings of the 5th Information Interaction in Context Symposium 2014
DOI: 10.1145/2637002.2637058
|View full text |Cite
|
Sign up to set email alerts
|

Personal information management and social networks re-finding on Twitter

Abstract: The following PhD project argues for analyzing Personal Information Management (PIM) behaviour on social networks and microblogging platforms, such as Twitter, as such services go far beyond their expected usage and have grown a viable source of information to many users. Of the three main information interaction activities that characterise PIM (finding -keeping -re-finding), only the retrieval of information has received researcher attention on such services. However, recent literature suggests that other PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A mainly crowdsourced (Tellwut) survey of 606 tweeters in 2013/4 found that half favorited tweets. Users favorited a tweet to help them to find it later or to show approval of the tweet [ 32 ] [ 33 ]. There seems to be no research focusing on reasons for favoriting academic tweets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A mainly crowdsourced (Tellwut) survey of 606 tweeters in 2013/4 found that half favorited tweets. Users favorited a tweet to help them to find it later or to show approval of the tweet [ 32 ] [ 33 ]. There seems to be no research focusing on reasons for favoriting academic tweets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…X has basically turned into an important need for someone in looking for an answer (Liu & Jansen, 2013). This statement is reinforced by the opinion of Meier (2014) who says that among the finding -keeping -re-finding activities in personal information management, X is seen as useful for finding personal information (Meier & Elsweiler, 2014;Nurhadi, 2017).…”
Section: Page189mentioning
confidence: 99%
“…Also, certain design of platforms could contribute to better information management (Meier, 2018; Ha et al , 2017). For example, favouriting is a function featured with personal information management, which allows users to capture and organise information in a separate timeline to enable effective re-access (Meier and Elsweiler, 2014). Finally, since information activities on platforms result in digital repositories as cultural heritage for society and users themselves, facilitation of both long-term preservation and disposition of information for users should be provided by platforms (Acker and Kreisberg, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%